Dinamika Kinerja Tenaga Kependidikan di Universitas XYZ Yang Dipengaruhi Oleh Disiplin - Solehudin Solehudin (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2023)
This research aims to investigate the influence of work discipline on the performance of educational staff at XYZ University. The research was conducted using a quantitative approach with a survey method. The research sample consisted of 142 educational staff members who were randomly selected. Data collection was done using a questionnaire containing several questions about work discipline and the performance of educational staff. The survey results were collected and data analysis was performed using statistical analysis techniques, including validity and reliability tests, descriptive analysis, and simple linear regression analysis. The analysis results showed that there was a significant influence of work discipline on the performance of educational staff at XYZ University, accounting for 37.3%. Thus, work discipline has a significant influence on the performance of educational staff at XYZ University. In the long run, efforts to strengthen the culture of work discipline can improve the quality of educational services provided by the university and improve the university's image in the eyes of the public.